Clinical and epidemiological characterization of hospitalized patients for cardiovascular causes. (Salud, Arte y Cuidado, 2020)
The objective was to determine the clinical and epidemiological characteristics of patients hospitalized for cardiovascular causes at the Dr. José Ángel Álamo Military Hospital. The study is descriptive, with a quantitative approach, with a non-experimental, transectional design. The technique used was through the collection of direct data through medical records, where all the records of patients with inclusion criteria were taken. The results obtained: the age with the highest incidence was between 61 to 80 years, with a male sex predominance 56%, and female sex 44%. It was found that within the psychobiological habits 81% of the patients consume coffee, 59% of them smoke and 46% consume some type of alcoholic beverage. Regarding the important personal pathological antecedents, arterial hypertension stands out, 79%, Diabetes mellitus 25%, previous cerebrovascular disease 12%, nephropathies 10%. While in the family pathological history this Arterial Hypertension, Ischemic Heart Disease and Diabetes Mellitus, equally 21% of the subjects of studies Cerebrovascular Diseases 12% and with Heart Failure 4%. Within the hospitalization diagnoses, Arterial Hypertension and Diabetes Mellitus predominated, 25%, Cerebrovascular diseases 23%, Nephropathies 20%, Heart Failure 20%, Mixed Cardiopathies 16% and in smaller proportions Valvular heart disease, hypertrophic cardiomyopathy and Venous Insufficiency. Conclusion: cardiovascular diseases continue to have a high prevalence and a constant relationship with sociodemographic data, psychobiological habits, personal and family pathological antecedents.
Keywords: cardiovascular diseases; clinical epidemiology